Preparation and performance evaluation of fluorescent nanofluid for oil displacement - Qi Gong; Haitao Li; Xin Ma; Jiating Hao; Fangjun Jia; Hongwen Luo; Sujuan Gao (Scientific Reports)
Abstract Oil displacement agent technology is an attractive technique for improving oil recovery efficiency, as it not only enhances oil recovery efficiency and extends oilfield lifespan, but also helps reduce environmental impact and improve the precision of oilfield management. However, the application of traditional oil displacement agents in oilfield development is limited by poor local fluidity and difficulty in monitoring their effectiveness. To improve oil displacement efficiency and achieve more accurate process monitoring, this paper designs an oil displacement agent that has both oil displacement and tracer functions. In this work, we first synthesized a fluorescent nano displacement agent with an average particle size of 80 nm using an improved Stöber synthesis method and silane coupling agent surface modification theory and characterized it using characterization techniques. Finally, we evaluated the migration characteristics, oil displacement performance, and tracer performance of the fluorescent nano displacement agent in the reservoir through core flow experiments. The results showed that the fluorescent nano displacement agent has good migration ability, with an improved recovery efficiency of 14.09%. The error between the fitted permeability and the actual permeability of the core in the experiment was about 10%. The simulation results once again proved that the fluorescent nano displacement agent can be used for tracer testing.